2012
DOI: 10.2141/jpsa.011120
|View full text |Cite
|
Sign up to set email alerts
|

Biological Features of the Avian Male Gamete and their Application to Biotechnology of Conservation

Abstract: Male gamete biology shows specific features in birds that contribute to the reproductive strategy of flying animals adapted to highly variable environmental conditions. In this paper, we review the main characteristics of bird sperm, their selection and storage in the highly specialized female oviduct, specific features of polyspermic fertilization, and the consequences of these biological adaptations on semen biotechnology. Among other features, the storage of sperm in specific oviducal glands is a key factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
37
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 62 publications
1
37
0
Order By: Relevance
“…Polge (1951), therefore, dialyzed chicken semen to reduce the glycerol concentration, and 35 live chicks were successfully produced. Since then, a number of studies of freezing of chicken semen using glycerol as a cryoprotective agent have been conducted (For review, see Donoghue and Wishart, 2000;Long, 2006;Blesbois, 2007Blesbois, , 2012.…”
Section: Semen Cryopreservationmentioning
confidence: 99%
“…Polge (1951), therefore, dialyzed chicken semen to reduce the glycerol concentration, and 35 live chicks were successfully produced. Since then, a number of studies of freezing of chicken semen using glycerol as a cryoprotective agent have been conducted (For review, see Donoghue and Wishart, 2000;Long, 2006;Blesbois, 2007Blesbois, , 2012.…”
Section: Semen Cryopreservationmentioning
confidence: 99%
“…Plus, the commercial breeds used for meat or egg production are genetically uniform but their genetic background differs between the two production types. Using chicken as an experimental model for male fertility has the added advantage of the direct application of results in order to help developing reproduction strategies for poultry breeders and to better characterize semen for bird genetic biodiversity preservation programs (24). Our previous results indicated that sperm cells ICM-MS profiling coupled with top-down HRMS could be employed as a fertility screening tool.…”
mentioning
confidence: 99%
“…In fowl, studies have demonstrated that the sperm gradually acquire the capacity for survival and fertilization in the male reproductive tract during their passage from the testis to the distal vas deferens (Ahammad et al, 2011a(Ahammad et al, , 2011b, whereas the oviduct provides an environment suitable for the resident sperm to retain their survival and fertility potential over an extended period (Yoshimura et al, 1997;Bré que et al, 2003;Bakst, 2011;Blesbois, 2012). In the oviduct, the SST that are typically located at the junction between the uterus and vagina, referred to as UVJ-SST, are the primary sites for sperm residence, and store the sperm more efficiently than the SST located in the infundibulum (Brillard, 1993;Bakst et al, 1994).…”
Section: Introductionmentioning
confidence: 99%